Edible green infrastructure: An approach and review of provisioning ecosystem services and disservices in urban environments (2017)
Recently published green infrastructure, nature-based solutions, and ecosystem disservices (ED) literature have focused primarily on the supply of urban regulating and cultural ecosystem services (ES). Other literature on urban and peri-urban agriculture has mostly studied the role of localized, intensive agricultural practices in providing food to inhabitants. The aim of this review is to raise awareness and stress the knowledge gap on the importance of urban provisioning ES, particularly when implementing an edible green infrastructure (EGI) approach as it can offer improved resilience and quality of life in cities. We compiled and systematically analyzed studies on urban ES and ED related to a number of EGI typologies. Our systematic review of the relevant literature via an EGI framework, identified more than 80 peer-reviewed publications that focused on ES and food production in urban areas. An EGI approach can contribute socially, economically, and environmentally to urban sustainability and food security. However, such benefits must be weighed against ED trade-offs, including: potential health risks caused by human exposure to heavy metals and organic chemical contaminants often present in urban surroundings. We conclude with recommendations and guidelines for incorporating EGI into urban planning and design, and discuss novel areas for future research. © 2017 Elsevier B.V.